Where Endemism Meets Urgency: Native Cactaceae and the Conservation Crisis in the Subtropical South America Pampa - Alessandra Almeida de Menezes; Eugenia Jacira Bolacel Braga; João Iganci (Diversity)
The subtropical grasslands of South America are known as Pampa, span parts of Brazil, Uruguay, and Argentina, and are undergoing rapid and alarming transformations due to agricultural expansion, habitat fragmentation, and climate change. Despite this, these areas harbor a remarkable diversity of Cactaceae, including a high proportion of endemic and threatened species. This study offers the first comprehensive inventory of native and endemic cactus taxa in the Pampean province of the Chacoan domain, integrating data from georeferenced herbarium records, biodiversity databases, and fieldwork. A total of 111 native taxa were identified, of which 62% are endemic to the region. Spatial analyses reveal that many species occur outside protected areas, with hotspots of richness and endemism located near international borders and in poorly studied regions. These findings underscore the urgent need to reassess conservation priorities in Pampa, where biodiversity is being lost at an accelerating pace. By identifying critical areas for conservation and highlighting gaps in species assessments, the present study contributes essential data to support public policy, conservation planning, and the establishment of cross-border strategies for the protection of this unique and vulnerable flora.